Islamic Republic of Mauritania : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes various aspects of fiscal framework in the Republic of Mauritania. Mauritania needs to avoid pro-cyclical fiscal policies and adopt rules that guide medium-term fiscal sustainability. Fiscal policy has been responsible and focused on fiscal consolidation, but important challenges lie ahead linked to price volatility, exhaustibility of resources, and effective use of resources. Mauritania has important natural resource wealth, and its fiscal policy is shaped by considerations resulting from its reliance on resource revenues. Prospects for price shocks in the short term and significant mining expansion in the long term could pose significant challenges to fiscal policy management. The analysis of fiscal framework options reveals that a fiscal rule which targets a nonresource primary balance for long-term sustainability, designed to allow some frontloading of public spending on productive investment, would be appropriate for Mauritania under the assumption of a finite resource horizon. A fiscal rule targeting a structural resource balance would be appropriate in the scenario of long-lasting resources, possible under the assumption of favorable developments in the global commodity markets.